2001
DOI: 10.1021/ol016526l
|View full text |Cite
|
Sign up to set email alerts
|

NiCl2(PCy3)2:  A Simple and Efficient Catalyst Precursor for the Suzuki Cross-Coupling of Aryl Tosylates and Arylboronic Acids

Abstract: NiCl(2)(PCy(3))(2) associated with PCy(3) promotes the selective cross-coupling of aryltosylates with arylboronic acids under relatively mild reaction conditions, and a variety of functional groups are tolerated in both arenes. This is one of the simplest and most efficient experimental procedures for the coupling of arylboronic acids with aryl tosylates reported to date. Reaction: see text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
116
2
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 298 publications
(124 citation statements)
references
References 17 publications
4
116
2
2
Order By: Relevance
“…The Hammett s À parameter [76,77] is an excellent descriptor in this case. Note, however, that the literature contains diverse reports: Similar correlations were reported for Suzuki, [78][79][80] Heck, [81][82][83][84][85] and carbonylation reactions [86] even though different Hammett parameters were used: Milstein and Herrmann reported that s À p parameters yielded the best fits, whereas other studies applied s p parameters. Even a s þ p correlation to establish a stabilization of a positive charge in the transition state was reported.…”
mentioning
confidence: 61%
“…The Hammett s À parameter [76,77] is an excellent descriptor in this case. Note, however, that the literature contains diverse reports: Similar correlations were reported for Suzuki, [78][79][80] Heck, [81][82][83][84][85] and carbonylation reactions [86] even though different Hammett parameters were used: Milstein and Herrmann reported that s À p parameters yielded the best fits, whereas other studies applied s p parameters. Even a s þ p correlation to establish a stabilization of a positive charge in the transition state was reported.…”
mentioning
confidence: 61%
“…70 This reaction was, however, restricted to mesylates and tosylates containing EWGs. Recently, Monteiro and co-workers 71 have reported the use of the NiCl 2 (PCy 3 ) 2 catalyst in the SM cross-coupling reaction of a variety of aryl tosylates with arylboronic acid under mild reaction conditions (Scheme 28).…”
Section: Sm Cross-coupling Reactions With Other Novel Palladium Catalmentioning
confidence: 99%
“…45 Nickel carboxyl cellulose (NiCC) was also evaluated for the Suzuki coupling reactions. 46 First, a test was performed for 6 h in the absence of ligands; however, no coupling product was formed. Based on this preliminary result for this reaction, it was performed again for a longer time, according to the literature, in the presence of triphenylphosphine.…”
Section: Pd-cc and Ni-cc Cross Coupling Reactionsmentioning
confidence: 99%